2017
DOI: 10.1002/bip.23029
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of melanoma metastasis by dual‐peptide PLGA NPS

Abstract: Despite the positive results observed in vitro and in vivo, clinical trials with bioactive peptides are generally hampered by their fast degradation in the biological system. Two bioactive peptides, P20 (CSSRTMHHC) and the combined peptide C (CVNHPAFACGYGHTMYYHHYQHHL) have been identified as anticancer therapeutics. Combined peptide C consists of peptide C (CVNHPAFAC), a tumor-homing peptide, conjugated to the antiangiogenic peptide HTMYYHHYQHHL with a GYG. In this work, PLGA NPs with peptide C were applied as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
1
7
0
Order By: Relevance
“…PLGA NPs without any encapsulated molecule were prepared by using a single emulsion-solvent evaporation method as described elsewhere [27]. Firstly, an organic solution of 100 mg of PLGA in 4 mL of DMF was prepared.…”
Section: Synthesis Of Plga Npsmentioning
confidence: 99%
“…PLGA NPs without any encapsulated molecule were prepared by using a single emulsion-solvent evaporation method as described elsewhere [27]. Firstly, an organic solution of 100 mg of PLGA in 4 mL of DMF was prepared.…”
Section: Synthesis Of Plga Npsmentioning
confidence: 99%
“…[360] [353] Salinomycin Anti-CD20 aptamers Specific binder targeting (CD20 is is a marker of melanoma-initiating cells)…”
Section: Multifunctional Delivery Systemsmentioning
confidence: 99%
“…In the last period, several publications highlighted the efficiency of PLGA-NPs in delivering anticancer agents; in a recent work, Arruda and his co-workers showed that the encapsulation of a peptide with antitumoral activity, P20 (CSSRTMHH), within the PLGA-NPs conjugated to the C peptide with a homing function (CVNHPAFACGYGHTMYYHHYQHHL), strongly increases their functionality. The therapeutic effect of these NPs was evaluated in a syngeneic model of metastasis and was shown to produce the same inhibitory effect of free P20 at fivefold higher concentration, reducing by 28% the number of lung nodules [ 21 ].…”
Section: Nanoparticles and Drug Deliverymentioning
confidence: 99%